Effect of exchange rate volatility on trade in Sub-Saharan Africa - Bernardin Senadza; Desmond Delali Diaba (Journal of African Trade, 2017)
The volatile nature of exchange rates with the advent of floating regimes has received much attention in economic research. The volatility is generally perceived as negatively affecting international trade. While theoretical predictions and empirical outcomes appear mixed, the balance seems to tilt in favour of this perception. Applying the pooled mean-group estimator of dynamic heterogeneous panels technique to data for eleven Sub-Saharan African economies over the period 1993 to 2014, this paper uncovers no significant effects of exchange rate volatility on imports. In the case of exports, however, the study finds a negative effect of volatility in the short-run, consistent with the above view, but a positive impact in the long-run.
Keywords: F1; F310; F320; 330; Exchange rate volatility; Trade flows; Pooled mean group estimator; Sub-Saharan Africa